2020
DOI: 10.1108/imds-08-2019-0417
|View full text |Cite
|
Sign up to set email alerts
|

Inventory financing a risk-averse newsvendor with strategic default

Abstract: PurposeThe paper aims to explore the optimal strategies of inventory financing when the risk-averse retailer has different objectives, in the presence of multi-risk, i.e. demand risk, non-operational risk and retailer's strategic default risk.Design/methodology/approachThis paper develops an inventory financing model consisting of a bank and a risk-averse retailer with strategic default. This paper considers two scenarios, i.e. the capital-constrained retailer cares about its profit or firm value. In the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Depending on which kind of credit financing is considered, two strategies are described. When financing is sourced from a bank, it is known as bank credit financing (BCF strategy) which mainly focuses on the perspective of coordination contracts (Ding and Wan 2020 ; Shi et al 2020 ), inventory decisions (Chakuu et al 2020 ; Li et al 2020a , b ; He et al 2020 ), information sharing (Li et al 2019 ; Sang 2021 ), etc. For the BCF strategy, Zhou et al ( 2020 ) explored the equilibrium of guarantor financing for retailers who can borrow bank credit in a four-stage supply chain structure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on which kind of credit financing is considered, two strategies are described. When financing is sourced from a bank, it is known as bank credit financing (BCF strategy) which mainly focuses on the perspective of coordination contracts (Ding and Wan 2020 ; Shi et al 2020 ), inventory decisions (Chakuu et al 2020 ; Li et al 2020a , b ; He et al 2020 ), information sharing (Li et al 2019 ; Sang 2021 ), etc. For the BCF strategy, Zhou et al ( 2020 ) explored the equilibrium of guarantor financing for retailers who can borrow bank credit in a four-stage supply chain structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yan et al ( 2018 ) explored the influences of product durability on the strategies of channel encroachment under the oligopoly market structure, and found that both members benefited from channel encroachment if the product durability is at a threshold level. On this basis, Li et al ( 2020a , b ) illustrated the interactions between channel encroachment and retail inventory under the scenarios of centralization and decentralization. In addition, for multiple downstream firms, Guan et al ( 2019 ) analyzed the relationship between channel encroachment and retail inventory to find that each member could obtain more profit for retail competition.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As a traditional resource of monitoring, fixed assets in SME business loans can be provided by either a firm or a firm's owner, in forms such as real estate, motor vehicles and equipment (Niinimaki, 2016). As an additional resource for monitoring, inventory and accounts receivable are studied by more researches as working capital collateral (Chen et al, 2017;Li et al, 2020). To monitor collaterals effectively and guarantee their liquidation value ,the practice should rely heavily on contractual regulations that formulate the delivery of goods, information flow and the negotiable instruments of financial flows (Hofmann and Belin, 2011).…”
Section: Supply Chain Financing Risk Managementmentioning
confidence: 99%